2016
DOI: 10.21548/34-2-1103
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Aroma Volatiles in a Red Wine with Low Sulphur Dioxide by a Mixture of Glutathione, Caffeic Acid and Gallic Acid

Abstract: The levels of several esters and other volatiles in Merlot-Cabernet Sauvignon blend red wines with typical sulphur dioxide (35 mg/L), with low sulphur dioxide (25 mg/L), and with low sulphur dioxide (25 mg/L) plus a mixture of antioxidants (glutathione 20 mg/L, caffeic acid 60 mg/L and gallic acid 20 mg/L), were evaluated at bottling, and after 18 and 36 months of ageing. Most volatiles decreased during wine storage. At bottling and after 18 months of storage, all three wines exhibited similar levels of volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Decreases in acetate esters and many ethyl esters have been observed during the ageing of wines, while other ethyl esters have increased or remained stable Roussis et al, 2007;Oliveira et al, 2008;Papadopoulou & Roussis, 2008). Similar behaviour of esters has been observed during the oxidative storage of wines (Ferreira et al, 1997;Roussis et al, 2005).…”
Section: Introductionsupporting
confidence: 56%
“…Decreases in acetate esters and many ethyl esters have been observed during the ageing of wines, while other ethyl esters have increased or remained stable Roussis et al, 2007;Oliveira et al, 2008;Papadopoulou & Roussis, 2008). Similar behaviour of esters has been observed during the oxidative storage of wines (Ferreira et al, 1997;Roussis et al, 2005).…”
Section: Introductionsupporting
confidence: 56%
“…Moreover, some compounds, such as glutathione, caffeic and gallic acids, can inhibit the decrease of some volatile compounds in wines during their storage, and the protective effect of these compounds increased in the presence of 40 mg/L of free SO 2 (Roussis & Sergianitis, 2008). It has been also observed that the mixtures of these compounds can protect several aromatic volatiles of white wines with reduced SO 2 (Roussis, Lambropoulos, & Tzimas, 2007). The results showed that the use of HT as alternative to SO 2 did not modify the global aromatic profile of wines, regardless of their origin.…”
Section: Volatile Compoundsmentioning
confidence: 98%
“…Glutathione is also capable of carrying out nucleophilic reactions with other compounds such as aldehydes (Cheynier et al, 1986;Cheynier & Van Hulst, 1988;Sonni et al, 2011) and has protective abilities toward important aroma compounds such as esters, monoterpenes and volatile thiols (Papadopoulou & Roussis, 2001;Lavigne-Cruège & Dubourdieu, 2003;Roussis et al, 2007;Papadopoulou & Roussis, 2008). However, GSH has also been shown to induce the production of H 2 S during wine ageing under lowoxygen conditions (Ugliano et al, 2011).…”
Section: The Role Of Antioxidantsmentioning
confidence: 99%